Postpartum factors and natural fibroid regression - LAUGHLIN, Shannon K. (2011)
OBJECTIVE: Many fibroids regress with pregnancy or postpartum involution. We sought to identify factors that might inhibit or enhance this natural regression. STUDY DESIGN: We used a prospective cohort of women with fibroids (n=494) determined by ultrasound screening during the early first trimester identified from the Right from the Start study. Ultrasounds were repeated three to six months postpartum (n=279). Logistic regression analyses were used to identify factors associated with fibroid regression (>50% reduction in volume). RESULTS: Postpartum progestin users had significantly less fibroid regression (p=0.01), while there was no association for combined estrogen-progestin use. Cesarean delivery and fever (hypothesized to inhibit regression) and breast feeding (hypothesized to enhance regression) were not associated with fibroid regression. CONCLUSION: Progestin use in the postpartum period may limit regression of fibroids, consistent with prior literature on progesterone's role in fibroid development. Research into progestin-only treatments in critical reproductive periods is needed.